INCREASED NOVELTY-INDUCED MOTOR ACTIVITY AND REDUCED DEPRESSION-LIKE BEHAVIOR IN NEUROPEPTIDE Y (NPY)–Y4 RECEPTOR KNOCKOUT MICE - TASAN, R. O. (2008)
There is growing evidence that neuropeptide Y (NPY) acting through Y1 and Y2 receptors has a prominent role in modulating anxiety- and depression-like behavior in rodents. However, a role of other Y-receptors like that of Y4 receptors in this process is poorly understood. We now investigated male Y2, Y4 single and Y2/Y4 double knockout mice in behavioral paradigms for changes in motor activity, anxiety and depression-like behavior. Motor activity was increased in Y2, Y4 and Y2/Y4 knockout mice under changing and stressful conditions, but not altered in a familiar environment. Y4 and Y2 knockout mice revealed an anxiolytic phenotype in the light/dark test, marble burying test and in stress-induced hyperthermia, and reduced depression-like behavior in the forced swim and tail suspension tests. In Y2/Y4 double knockout mice, the response in the light/dark test and in the forced swim test was further enhanced compared with Y4 and Y2 knockout mice, respectively. High levels of Y4 binding sites were observed in brain stem nuclei including nucleus of solitary tract and area postrema. Lower levels were found in the medial amygdala and hypothalamus. Peripheral administration of pancreatic polypeptide (PP) induced Y4 receptor-dependent c-Fos expression in brain stem, hypothalamus and amygdala. PP released peripherally from the pancreas in response to food intake, may act not only as a satiety signal but also modulate anxiety-related locomotion.